2017
DOI: 10.3389/fnagi.2017.00380
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking Neurocognitive Substrates of Late-Life Affective Symptoms Using the Research Domain Criteria: Worry Is an Essential Dimension

Abstract: While investigations have sought to identify the distinct and shared contributions of anxiety and depression to neurocognitive processes in late life, less is known regarding the further contribution of worry, a unique and critical dimension of affective dysregulation. Capturing the full range of symptoms, as inspired by the NIH Research Domain Criteria (RDoC), may provide finer-grained information on inter-relationships among worry, anxiety and depression on neurocognitive processing in later life. The object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
1
5
1
Order By: Relevance
“…There is some evidence in the literature to support an enhancing effect of worry on performance. Beaudreau et al (2017) found that elevated worry improved performance on tests of cognitive control and delayed verbal memory in older adults with anxiety or depression; however, this effect was only found among participants with high levels of depressive symptoms, which would not be consistent with the current findings given low depressive symptoms in the current sample. The processing efficiency theory of anxiety (Eysenck & Calvo, 1992) may provide additional insight into these findings.…”
Section: Discussioncontrasting
confidence: 99%
“…There is some evidence in the literature to support an enhancing effect of worry on performance. Beaudreau et al (2017) found that elevated worry improved performance on tests of cognitive control and delayed verbal memory in older adults with anxiety or depression; however, this effect was only found among participants with high levels of depressive symptoms, which would not be consistent with the current findings given low depressive symptoms in the current sample. The processing efficiency theory of anxiety (Eysenck & Calvo, 1992) may provide additional insight into these findings.…”
Section: Discussioncontrasting
confidence: 99%
“…The Yerkes-Dodson law ( 61 ) proposed an inverted u-shaped relationship between the state of stress and cognitive performance, in which a proper amount of stress or arousal contributed to better cognitive function. In addition, Beaudreau et al ( 62 ), who found that worry attenuated the negative effect of depressive and anxiety symptoms on inhibitory control, suggested that the personality trait of perfectionism characterized by higher motivation for better performance and worry level could be a possible explanation. Moreover, it has been hypothesized that abnormalities in the functional connectivity between and within the executive control network (ECN) and the default mode network (DMN) ( 63 , 64 ) together with the failure of DMN deactivation during cognitive tasks ( 65 ) lead to negative cognitive bias and cognitive impairment in LLD subjects ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…If the stressor does facilitate better performance among older participants, it could be due to different manifestations of anxiety between age groups. For example, experimental work has demonstrated dissociable effects of these types of anxious symptoms on some cognitive tasks in older adults (65+ years; Beaudreau et al, 2017); such differences could extend to slightly younger adults (40-50 years) and mnemonic discrimination, a specific form of episodic memory.…”
Section: Discussionmentioning
confidence: 99%